Porou solids for biogas upgrading and CO2 sequestration - Silva, José A.C. (2013)
In this work, we will present sorption equilibrium, kinetic and fixed bed data of CO2, CH4 in MOF-508b and zeolite 13X at 303, 323 and 343 K and partial pressures up to 4.5 bar. These data are fitted with appropriate isotherm models. At the same time single, binary and ternary breakthrough curves were measured to provide required data to develop and validate a mathematical model based on the LDF approximation for the mass transfer, which could be used in the implementation (simulation) of a cyclic adsorption processes (PSA) for the purification of biogas and CO2 sequestration.